(untitled) (Palíndromo, 2026)
Starting from reflections on the construction of the gaze within the cishetero-Western visual regime and, more specifically, on lesbian invisibility in the visual arts, I propose analytical-visual categories that connect contemporary artistic practices with historical traces of dike art. These categories are organized into five panels of images: Portrait of the Beloved, The Couple, Lesbian Portrait, Sapabonde, and Counter-Archives. Each panel activates theoretical, aesthetic, and political discussions that, while interconnected, can be read independently. This is a visual and conceptual curatorship open to wandering, multiplicity, and proliferation. At stake is not only the presence of dikes in art history but the possibility of reconfiguring the terms of in/visibility, reorganizing the sensible world, and intervening in collective memory.